Studies in regard to the classification and putative toxicity of Fridericia japurensis (Arrabidaea japurensis) in Brazil. (1st June 2016) - Lima, Everton F.; Medeiros, Rosane Maria T.; Cook, Daniel; Lee, Stephen T.; Kaehler, Miriam; Santos-Barbosa, Joyce M.; Riet-Correa, Franklin
Abstract: Numerous plant species worldwide including Palicourea marcgravii (Rubiaceae) and Tanaecium bilabiatum (Bignoniaceae) in Brazil cause acute cardiac failure (sudden death) and are known to contain monofluoroacetate (MFA). Other Bignoniaceae species including Fridericia japurensis ( Arrabidaea japurensis ) are reported to cause sudden death in livestock in the Brazilian state of Roraima and are suspected to contain MFA due to the similarity of clinical signs. In this study herbarium specimens of Fridericia japurensis and field collections suspected to be F. japurensis were analyzed for MFA, and plant material from the field collections was dosed to rabbits. No MFA was detected in the herbarium specimens authoritatively identified as F. japurensis ; however, MFA was detected in the field collections, which were identified as T. bilabiatum . Rabbits dosed orally with T. bilabiatum died acutely. Voucher toxic specimens initially described as F. japurensis were incorrectly identified, and the correct botanical name for this plant is T. bilabiatum ( Arrabidaea bilabiata ). Based on this study we conclude that there are no data to support the toxicity of F. japurensis and that the plant previously reported under this name as causing acute cardiac failure in cattle in Roraima is T. bilabiatum. This research highlights the importance of voucher specimens as part of any toxic plant investigation and corrects the literature regarding these toxic plants. Highlights: Fridericia japurensis is reported to cause sudden deaths in cattle in northern Brazil. No monofluoracetate (MFA) was detected in herbarium specimens of F. japurensis. Toxic plants suspected of being F. japurensis were identified as Tanaecium bilabiatum. MFA-containing herbarium species of F. japurensis were reclassified as T. bilabiatum. It is important to keep voucher specimens of any toxic plant investigation.